The impacts of Brewer-Dobson and Hadley circulation on tropospheric ozone variations over three city clusters in China - Zhang, Xin; Zhang, Xingying; Zhou, Lihua; Cao, Xifeng; Deng, Zhili; Jiang, Yuhan (Atmospheric research, 2023)
The positive trend of tropospheric column ozone (TCO) in China has been confirmed by numerous observations, particularly in the rapidly developing city clusters such as Beijing-Tianjin-Hebei (BTH), the Yangtze River Delta (YRD) and the Pearl River Delta (PRD). An unignorable but poorly known function may be played by the Brewer-Dobson circulation (BDC) and the Hadley circulation (HC), both of which are in their strengthening phase. This study discusses their connection to TCO in these three city clusters based on a novel and powerful causal analysis method Convergent Cross Mapping (CCM). It revealed that both BDC and HC exerted substantial causal effects on the variations of the TCO in BTH, the YRD, and the PRD. The upwelling moving northward in the summer substantially lowered TCO in the PRD, contributing to the difference in the TCO annual cycle characteristics between northern and southern China. Besides, CCM distinguished that hemispheric HC impacts TCO greatly more than total HC, and the most essential branches of BDC were stratospheric or shallow branches. The BDC and HC indices determined by CCM were used for building a multiple linear regression model, which assessed their importance for long-term changes in regional TCO. The intensity of BDC is the most important influencing factor in each region, particularly in the YRD. BTH is mainly affected by the intensity of the two meridian circulations. The influence of the widths of meridional circulation upwellings on TCO in the PRD cannot be ignored. Furthermore, TCO displayed significant positive trends during 2005–2020, with rates of 2.3 ± 0.4, 2.5 ± 0.4, and 2.7 ± 0.5 DU/decade in BTH, the YRD, and the PRD, respectively. •BDC and HC contribute to the different annual cycle patterns of TCO in northern and southern China.•Hemispheric HC impacts TCO greatly more than total HC.•The upwelling moving northward in the summer substantially lowered TCO in the PRD•TCO showed positive trends of around 2.5 DU/decade in China from 2005 to 2020